THE ADAPTED COGNITIVE - BEHAVIORAL THERAPY FOR THE REHABILITATION OF PATIENTS AFTER MYOCARDIAL INFARCTION - Djalilova S. Kh,; Ibodullaev Z.R,; Sadikova S.I, (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to evaluate the effect of an adapted cognitive – behavioral therapy (CBT) on quality of life of patients with myocardial infarction, as well as their psycho-emotional state. According to HADS of the clinically expressed anxiety - depressive disorder, in the main and comparative groups, are approximately equal (1,2\1,3). Subjective data of patients of the main group improved 2 times, psycho-emotional state 2,5 times, stress adaptation increased in 76% of patients in this group. The psycho-emotional state of patients in the comparison group in dynamics (on the 10th day) improved 1.7 times, however, subjective symptoms also they showed maladaptive behavior coincided. The study of the quality of life of patients in both groups according to the SF-36 protocol showed that in the main group with a tendency to highly effective and persistent correction of psycho-emotional disorders in patients after myocardial infarction.